Reading as therapy : what contemporary fiction does for middle-class Americans - Aubry, Timothy Richard, 1975- (University of Iowa Press, 2011)
Why do Americans read contemporary fiction? This question seems simple, but is it? Do Americans read for the purpose of aesthetic appreciation? To satisfy their own insatiable intellectual curiosities? While other forms of media have come to monopolize consumers' leisure time, in the past two decades book clubs have proliferated, Amazon has sponsored thriving online discussions, Oprah Winfrey has inspired millions of viewers to read both contemporary works and classics, and novels have retained their devoted following within middlebrow communities.